Instructive Role of the Microenvironment in Preventing Renal Fibrosis. (5th October 2016) - Matsumoto, Kei; Xavier, Sandhya; Chen, Jun; Kida, Yujiro; Lipphardt, Mark; Ikeda, Reina; Gevertz, Annie; Caviris, Mario; Hatzopoulos, Antonis K.; Kalajzic, Ivo; Dutton, James; Ratliff, Brian B.; et al.
Abstract: Accumulation of myofibroblasts is a hallmark of renal fibrosis. A significant proportion of myofibroblasts has been reported to originate via endothelial-mesenchymal transition. We initially hypothesized that exposing myofibroblasts to the extract of endothelial progenitor cells (EPCs) could reverse this transition. Indeed, in vitro treatment of transforming growth factor- β 1 (TGF- β 1)-activated fibroblasts with EPC extract prevented expression of α -smooth muscle actin ( α -SMA); however, it did not enhance expression of endothelial markers. In two distinct models of renal fibrosis—unilateral ureteral obstruction and chronic phase of folic acid-induced nephropathy—subcapsular injection of EPC extract to the kidney prevented and reversed accumulation of α -SMA-positive myofibroblasts and reduced fibrosis. Screening the composition of EPC extract for cytokines revealed that it is enriched in leukemia inhibitory factor (LIF) and vascular endothelial growth factor. Only LIF was capable of reducing fibroblast-to-myofibroblast transition of TGF- β 1-activated fibroblasts. In vivo subcapsular administration of LIF reduced the number of myofibroblasts and improved the density of peritubular capillaries; however, it did not reduce the degree of fibrosis. A receptor-independent ligand for the gp130/STAT3 pathway, hyper-interleukin-6 (hyper-IL-6), not only induced a robust downstream increase in pluripotency factors Nanog and c-Myc but also exhibited a powerful antifibrotic effect. In conclusion, EPC extract prevented and reversed fibroblast-to-myofibroblast transition and renal fibrosis. The component of EPC extract, LIF, was capable of preventing development of the contractile phenotype of activated fibroblasts but did not eliminate TGF- β 1-induced collagen synthesis in cultured fibroblasts and models of renal fibrosis, whereas a receptor-independent gp130/STAT3 agonist, hyper-IL-6, prevented fibrosis. In summary, these studies, through the evolution from EPC extract to LIF and then to hyper-IL-6, demonstrate the instructive role of microenvironmental cues and may provide in the future a facile strategy to prevent and reverse renal fibrosis.